Industrial automation: the use of robots in logistics processes - Siqueira, Stella Caroline de Jesus (2025)
This research was conducted through a bibliographic review methodology. The study focuses on the use of robots in logistics processes, addressing how robotic automation is transforming efficiency and competitiveness in this sector. The main objectives consist of exploring the contributions of AGV robots (Automated Guided Vehicles) and RPA (Remotely Piloted Aircraft) within logistics, evaluating how these technologies optimize time and reduce costs, which are crucial elements for competitiveness in the market. The methodology employed was exploratory and bibliographic, utilizing extensive literature to understand the expansion and implications of robotics in logistics. The results confirm that AGV and RPA robots are playing significant roles, with AGVs improving storage and RPAs facilitating fast and secure deliveries. The discussion suggests that the implementation of these technologies not only enhances operational efficiency but also presents a strategic differential for companies seeking innovation and market leadership. The research reaffirms that automation is a growing and beneficial trend, essential for the future of global logistics.